Composição de formação: narrativas (auto)biográficas como acordes do formador-professor - Schiavon, Tatiana de Camargo (2020)
The field of formation of the trainer is a recent theme and still little investigated in the educational literature, which justifies the importance of this study. This work is configured as a research-training, because when performing the research one can live in itself the transformations mediated by the reflexive movement lived, as well as the awareness of the performance as teacher trainers, from the dialogy between the act of self-forming and ecoforming, recognizing the conviviality with the group and with the context. We sought, therefore, to answer the question: How do the teacher trainer training processes take place from the perspective of continued training from the dialogy between the act of training teachers and graduating? How does he act? How do you become a trainer? In view of the problem, the objectives aimed to know the profile of the trainers and the reasons that led them to constitute trainers; identify convergences and divergences in the relationship with the constitution of themselves in the lived experience, as well as to know the marks that integrate the process of forming and/or (self-forming), enabled a comprehensive and interpretative analysis of this process. With this, biographical (auto)biographical narratives were used, from the biographical studio device of the project, which underwent some alterations in order to potentiate the reflections. As theoretical and methodological input, Delory-Momberger (2006, 2011, 2012, 2014), Passeggi (2006, 2008, 2011, 2016), Josso (2002, 2007, 2008), among others, was used. The information obtained indicates that the group's formation movement covered cultural, social and political aspects, which mobilized the processes of learning to learn, which points to a need for training through the experiences lived, as well as the finding of a permanent formation in the face of the conjuncture of relationships that are established in intersubjectivity. The use of the biographical studio device of project made it possible to raise awareness of the group, leading participants to think about the constant learning to learn about themselves, which opportunistic one look not only at the path of learning itself, but of the other, in acting as teacher trainers. It results in a recognition that the trainer needs to be attentive to the needs of teachers and the context in which they act, in order to enable moments and spaces of reflection on the trajectories, finding strategies to problematize the various experiences so that they consolidate themselves in meanings, providing the other to experience in themselves processes of resignification that he himself lived. Keywords: formation of trainers; research-training; methodology (auto)biographical